Effects of Scallop Visceral Mass and Mantle as Dietary Supplements on the Growth, Immune Response and Intestinal Microflora of Juvenile Sea Cucumber Apostichopus japonicus - Yu Yu; Mengshu Wang; Yichao Ren; Xin Wang; Xiangyun Ge; Kecheng Li (Biology, 2023)
Scallop visceral mass and mantle are aquatic byproducts and waste, but they have high contents of protein. In this study, scallop visceral mass and mantle were used as supplements in the diet of juvenile sea cucumber (A. japonicus) and their effects on the growth, fatty acid and amino acid compositions, the non-specific immune responses and the intestinal microflora of A. japonicus were investigated through a 40 d feeding experiment. The results showed that dietary supplementation of scallop visceral mass significantly accelerated the specific growth rate (SGR) of juvenile A. japonicus by 3 times within 20 days, and also raised the contents of ω-3 fatty acids including EPA and DHA and the ω-3/ω-6 ratio of the sea cucumber tissue, which is favorable to the health and commercial value of the sea cucumber. Furthermore, it was found that the supplementation of scallop visceral mass and mantle stimulated the expression of immune-related genes and enhanced the immune defense in A. japonicus. Scallop visceral mass and mantle supplementation also increased the microbial diversity and the abundance of beneficial microbes including Bifidobacteriaceae, Streptomycetaceae, Clostridiaceae and Rhizobiales in the gut of A. japonicus. This study reveals the beneficial effects of dietary supplementation of scallop visceral mass and mantle on the growth of juvenile A. japonicus, which might be a promising way to reutilize this scallop waste and raise its economic value.